The attitudes to fertility and quality of life in relation to chemotherapy in young breast cancer survivors - Memon, Fouzia (Nepal Journal of Obstetrics and Gynaecology, 2014)
Background: Since a significant proportion of women treated for breast cancer will now survive their cancer, quality of life for survivors is an important issue. For many young women fertility will be a significant factor in this. A woman’s appreciation of her own fertility is likely to be a key factor and her own body image and self-esteem will influence both the type and success of relationships entered into. This in itself may have an effect on her decision to attempt to become pregnant and for a woman, who is already in a successful relationship, may have a role in the decision to start or complete a family. Methods: An Ovid-Medline search was carried out January 1996 to May 2007, looking for the following terms in the title or abstracts (breast cancer, fertility, psychological issues, sexuality, and quality of life). Results: The present review paper explored fertility concerns of young woman with breast cancer and related sexual and psychological effects that might affect their quality of life. Conclusion: This extensive literature review from medical databases like Ovid-Medline has revealed that among depression and physical and psychological stress, fear of loss of fertility is a major factor of poor quality of life among young premenopausal breast cancer survivors. DOI: http://dx.doi.org/10.3126/njog.v3i2.10823 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 4-7